2016
DOI: 10.1111/cei.12894
|View full text |Cite
|
Sign up to set email alerts
|

Urinary B cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL): potential biomarkers of active lupus nephritis

Abstract: B cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL) help in B cell activation, maintenance and plasma cell survival. B cell infiltration has been demonstrated in kidneys of patients with lupus nephritis (LN). Serum levels of BAFF and APRIL have shown inconsistent relationships with lupus disease activity. We evaluated urinary levels of BAFF and APRIL as biomarker for LN. Thirty-six patients with proliferative lupus nephritis (AN), 10 with active lupus without nephritis (AL) and 15 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…In a previous study, we have shown that there were no significant differences in serum levels of BAFF in SLE patients when compared to healthy controls, while the APRIL levels were even significantly decreased (Wardowska et al, 2020). As we suggested earlier, it is also possible that an increased APRIL gene expression in B cells of SLE patients (Wardowska et al, 2020), as well as in mDCs, as demonstrated here, is the result of feedback in response to urinary protein loss which is a phenomenon often described in SLE (Phatak et al, 2017).…”
Section: Serum Componentsupporting
confidence: 72%
“…In a previous study, we have shown that there were no significant differences in serum levels of BAFF in SLE patients when compared to healthy controls, while the APRIL levels were even significantly decreased (Wardowska et al, 2020). As we suggested earlier, it is also possible that an increased APRIL gene expression in B cells of SLE patients (Wardowska et al, 2020), as well as in mDCs, as demonstrated here, is the result of feedback in response to urinary protein loss which is a phenomenon often described in SLE (Phatak et al, 2017).…”
Section: Serum Componentsupporting
confidence: 72%
“…Therefore, it is necessary to identify non-invasive biomarkers that can be easily obtained and reflect current renal inflammation [ 34 ]. Over the last two decades, many clinical studies have demonstrated the presence of molecules associated with B-cell activation in the serum [ 29 , [35] , [36] , [37] ] and kidney tissues [ 24 , 26 , 28 , 38 ] of active LN patients. One study demonstrated that serum BAFF level was lower in SLE patients with nephrotic-range proteinuria than in SLE patients with less severe proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the selective blockade of BAFF prevents the development of LN in mice [ 23 ]. B-cell infiltration has also been demonstrated in the kidneys of proliferative LN patients [ 24 ], resulting in elevated renal BAFF and APRIL that can be detected in urinary sediment [ 25 ], suggesting potential utility of these factors as urinary disease biomarkers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several putative novel serum and urine biomarkers have been studied in LN. [104][105][106][107] These candidate markers must be studied in a prospective fashion, ideally in clinical trials. It is likely that biomarker panels will be required to accurately stratify risk, predict flare, determine treatment, monitor response to treatment, and predict prognosis.…”
Section: Pathogenesismentioning
confidence: 99%